Electrical Energy Management According to Pricing Policy: A Case in Vietnam - Thi Tuyet Mai Nguyen; Pham Nguyen Dang Khoa; Ngoc Anh Huynh (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Electrical equipment is increasingly diversified in both types and capacity to meet the maximum needs of people in the 4th industrial revolution. This development has helped people to achieve many great scientific achievements, but this development has led to a rapid increase in the demand for electric energy in recent years. The traditional electricity supply from fossil fuels is gradually depleting, which has prompted the search for clean and renewable energy sources to gradually replace the dependence on this energy source. Prosumer, HEMS (home energy management system), and other solutions have been researched and applied to optimize electrical energy sources. However, for countries that mainly use fossil energy sources like Vietnam, these solutions are not effective. Policy on the management could help to solve this problem, in particular, the price policy is the solution that Vietnam has used to effectively manage this energy source. This article analyzes the issues of applicable pricing policy in Vietnam, proposes potential policies to improve and protect the electric energy system, as well as enhances the rate of renewable energy use in the electricity system in Vietnam